PENGEMBANGAN E-MODUL BERBASIS AYAT AL-QURAN UNTUK MEMBIASAKAN KEMAMPUAN PROBLEM SOLVING SISWA - Hanuri Sakarti; Agung Hartoyo; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to develop e-modules based on the verses of the Qur'an and familiarize students with problem solving skills after using e-modules at SMAN 1 Sambas. The research method used was development research with the ADD model (Analize, Design, Develop). The research sample consisted of 28 students of class X MIPA 2. Based on the result, e-module was suitable for use in teaching and learning activities to apply the four core competencies. Students also begin to get used to using problem solving skills in learning.Keywords : E-Module, Problem Solving Skills, and Verses of the Quran